2011
DOI: 10.1038/ejhg.2011.216
|View full text |Cite
|
Sign up to set email alerts
|

Researchers’ opinions towards the communication of results of biobank research: a survey study

Abstract: Eighty Dutch investigators (response 41%) involved in biobank research responded to a web-based survey addressing communication of results of biobank research to individual participants. Questions addressed their opinion towards an obligation to communicate results and related issues such as ownership of blood samples, privacy, therapeutic relationship, costs and implications for participants. Most researchers (74%) indicated that participants only have to be informed when results have implications for treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 21 publications
(25 reference statements)
1
18
0
2
Order By: Relevance
“…33,50 Professionals shared the concerns about potential emotional and psychological harm to the patients in several quantitative and qualitative studies. 51,[53][54][55][56] Some felt that this could in turn lead to a loss of public trust in research institutions. 54 The most prominent concern of professionals was the complexity of the results, the uncertainty in their interpretation and concerns about the quality of information, including validity and clinical utility of genomic findings.…”
Section: Professionals/public N=2mentioning
confidence: 99%
See 1 more Smart Citation
“…33,50 Professionals shared the concerns about potential emotional and psychological harm to the patients in several quantitative and qualitative studies. 51,[53][54][55][56] Some felt that this could in turn lead to a loss of public trust in research institutions. 54 The most prominent concern of professionals was the complexity of the results, the uncertainty in their interpretation and concerns about the quality of information, including validity and clinical utility of genomic findings.…”
Section: Professionals/public N=2mentioning
confidence: 99%
“…While the public considered it an obligation to inform about research findings even if the results were not unambiguous 57 , most professionals agreed on the researcher's duty to return 'life-threatening' findings as well as findings on preventable or treatable diseases. 53,58 Information about the return of incidental findings from genomic research during the informed consent process. Very few qualitative studies with professionals and the public addressed whether returning incidental findings should be discussed with the participant during the informed consent process.…”
Section: Professionals/public N=2mentioning
confidence: 99%
“…[9][10][11][12][13] The ethical and legal appropriateness of different consent models is one of the most divisive topics with the absence of a consensus among academic scholars, 6 research policies, 14 and public opinion data. 15 While the bulk of research studies focus on capturing the perceptions of the general public and patients on research ethics issues related to biobanking, [16][17][18] only a few have focused on understanding the views of scientists who may manage biobanks [19][20][21][22][23][24][25] and even fewer concentrate on scientists' perceptions of informed consent. 26,27 It is important to capture the opinions of scientists as they run biobanks and are the end users of biorepository samples and information and thus have first-hand knowledge on biobank functions.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers feel that they have variable duties: in a recent study, most researchers (74%) indicated that participants have to be informed when results have implications for treatment or prevention (Meulenkamp et al, 2012). Within the context of pediatric biobanks, scholars regularly refer to children's right to an open future to restrict the return of results (Hens et al, 2011).…”
Section: Ethical Issues Related To the Return Of Resultsmentioning
confidence: 99%